Theoretical realization of tunable hollow beams using a periodical ring structure with a complex phase - Sun, Changwei; Wang, Quansen; Liang, Jing; Wang, Wencong; Liu, Dongmei; Chen, Zhenhua; Gu, Min (Frontiers in Physics, 2024)
Hollow beam is a peculiar structure beam, which has been widely used in various areas. Here, we propose a novel diffraction optical element to generate tunable hollow beams. This element is composed of periodic concentric rings. The phase of each ring is periodically distributed between −π and π and satisfies a complex variable function. By tuning the parameters of the structure, we can flexibly manipulate the size and length of the hollow beam. The length of the beam can be increased from 98 λ to 248 λ, and the full width at half maximum varies from 0.43 λ to 0.61 λ. Moreover, the light intensity and side lobe of the hollow beam can also be regulated using the designed diffraction optical element. The potential applications of this highly tunable hollow beam include optical nanomanipulation, microscopic imaging, and nanolithography.